Analisis Efektivitas dan Kontribusi Pajak Katering Terhadap Pendapatan Asli Daerah Kabupaten Magetan Tahun 2019-2023 - Dhamayanti, Yolanda (Universitas PGRI Madiun, 2025)
This study aims to determine the effectiveness and contribution of catering tax to PAD Magetan Regency. This research was conducted at BPKPD Magetan Regency. This study uses a qualitative descriptive research method with a case study approach by analyzing the target and realization of restaurant tax in 2019-2023. The results of the study indicate that the level of effectiveness of restaurant tax in 2019-2023 is very effective. The highest level of effectiveness in 2019 was 170.75% and the lowest level of effectiveness in 2023 was 124.95% with an average effectiveness of 148% which means that the percentage is very effective. The overall level of effectiveness of restaurant tax is included in the very effective criteria from year to year even though the percentage value decreases. The lowest percentage contribution in 2020 was 1.22% and the highest in 2023 was 1.94%. The average contribution of restaurant tax in the last 5 years of 1% is still in the criteria of contributing less, because the PAD of Magetan Regency is not fully received from restaurant tax in the catering sector.